Relationship Between Effectiveness of Teleworking and Job Performance on Online Shop Employees: Hubungan Antara Efektivitas Teleworking dengan Kinerja pada Karyawan Online Shop - Al-farisi, Haris; Ashshiddiqi, Ali Mahmud (Universitas Muhammadiyah Sidoarjo, 2024)
Employee performance influences company development. Like employees in general, the performance of online shop employees affects the productivity or effectiveness of the business carried out to achieve profits. Technology-based online shops require effective implementation of teleworking. Empirically, this research determines the relationship between the effectiveness of teleworking and the performance of online shop employees. Researchers put forward the hypothesis that there is a positive correlation between the effectiveness of teleworking and the job performance of online shop employees. The respondents for this research consisted of 101 online shop employees in Yogyakarta. Researchers used the Employee Performance Scale (EPS) compiled by Tabouli et al. (2016), and the E-Work Life Scale (EWL) from Grant et al. (2018). Data analysis through Pearson product moment revealed a significant relationship between teleworking effectiveness variables and performance variables (R=0.261 and p=0.008). These results indicate that the higher the effectiveness of teleworking, the higher the performance of online shop employees, and vice versa. The contribution of teleworking effectiveness to employee performance is only 0.068 or 6.8%, of which the remaining 93.2% is other influential variables. Researchers put forward implications and suggestions based on these findings. Highlights: Teleworking's impact: The study reveals a positive correlation between teleworking effectiveness and job performance among online shop employees. Data significance: Analysis indicates a significant relationship between teleworking effectiveness and employee performance. Contribution insight: Teleworking effectiveness contributes 6.8% to employee performance, with other factors playing a substantial role. Keywords: Employees, Effectiveness of Teleworking, Job Performance